Product Design Assistance Activities and Product Innovation Counseling and Digital Marketing in Community Service in Rejowinangun Village, Kademangan Sub-District, Blitar Regency - Purbasari, I. Y.; Sugiarto; R. Alit (Nusantara Science and Technology Proceedings)
Rejowinangun village in Blitar Regency has the slogan "Village of UMKM (MSME-Micro, Small, and Medium Enterprises)". This village has been a home of many MSMEs which provide jobs for local residents and ready to sale food production. This is in line with the development of tourism in the village of Plosorejo, Kademangan sub-district, Blitar Regency, namely Kampung Coklat, which increases the number of MSMEs in the Kademangan District area. Rejowinangun village is one of the main supplier of Kampung Coklat. Unfortunately, this increase was not accompanied by an increase in sales. The number of MSMEs is increasing but the level of sales is declining, due to the increase in MSMEs which offer the same products as that of the current MSMEs, while the marketing area is not expanding. The lack of mastering good marketing techniques, as well as the lack of technological knowledge to do electronic marketing are said to be the cause, so that these small business operators can only rotate in the area where the MSMEs are established. On the other hand, these MSMEs have rather poor method in terms of packaging design, which are less attractive and do not provide more information for prospective buyers. Another cause is that local tourists or prospective consumers have no information about where to buy products directly from local residents, apart from the tourism place there, even though the prices offered by MSMEs are so much cheaper than that of in the tourism galleries or outlets. This community service scheme aimed to help the MSMEs in Rejowinangun village to increase their revenue by providing better and more attractive product designs and expand their marketing strategy to make use of digital marketing. New designs have been created and a web-based application has been developed to help MSMEs reach a broader market outside their village, or even outside Blitar Regency. After the deployment of the new designs and the use of digital marketing, they are still being monitored periodically about the development of their product marketing results.